Results of Trabecular-Metal Total Ankle Arthroplasties With Transfibular Approach. (April 2020) - Tiusanen, Hannu; Kormi, Sami; Kohonen, Ia; Saltychev, Mikhail
Background: Total ankle arthroplasty is an alternative for arthrodesis. The objective of this study was to investigate the safety of trabecular-metal ankle prosthetic system with transfibular approach and external frame and its association with changes in clinical and functional scores. Methods: Between May 2013 and June 2017, a total of 104 consecutive patients underwent primary total ankle arthroplasty with a trabecular metal implant. The prospective clinical and radiographic data were collected. The mean follow-up time was 43.6 (14.6) months. Results: Of 104 patients, 88 (89%) reported improved functioning and 65 (66%) were very satisfied with the surgery. Of the patients, 51 (50%) did not report any pain at the end of follow-up at all. The average Kofoed score was 37.6 (SD 17.4) points at baseline and 74.8 (SD 20.6) points at the end of follow-up. There were 37 additional procedures, and the complication rate was nearly 20%. Conclusion: Trabecular-metal total ankle prosthesis showed promising clinical results concerning pain and function. At 5-year follow-up, osteolysis and component loosening were rare. Level of Evidence: Level IV, case series.